Assessing Suicidal Ideation Using a Brief Self-Report Measure. (March 2021) - Terrill, Douglas R.; Rodriguez-Seijas, Craig; Zimmerman, Mark
Highlights: A low level of agreement was found between assessment measures. Self-report SI items demonstrated low PPV for passive and active SI. Self-report SI items demonstrated high NPV for passive and active SI. Self-report SI items were strongly correlated with same-domain interview ratings. Abstract: Accurate assessment of suicidal thoughts is a challenge for researchers and clinicians. There is evidence that self-report and clinical interview assessment methods can result in different endorsement numbers when used to assess suicidal ideation. This study investigates endorsement rates and psychometric properties of a two-item self-report measure of suicidal ideation that distinguishes active from passive suicidal ideation, when compared with a clinical interview. Individuals presenting at an outpatient psychiatry clinic completed a measure of depression severity containing two items assessing passive and active suicidal ideation before undergoing a structured clinical interview. Self-report and clinical interview items demonstrated a low level of agreement. Self-report items were more strongly correlated with same-domain clinical interviewer ratings than different-domain ratings. These items demonstrated high negative predictive value and moderate-to-low positive predictive value for interviewer ratings. A two-item measure of suicidal ideation did not highly align with corresponding interviewer ratings, though such a measure may be useful in determining the absence of suicidal ideation, as well as distinguishing between passive and active suicidal ideation.